ENVIRONMENTAL PERFORMANCE AND CSR DISCLOSURE ON FIRM VALUE THROUGH FINANCIAL PERFORMANCE - Devi Edriani (Economica, 2024)
This research aims to analyze the effect of environmental performance and corporate social responsibility (CSR) disclosure on firm value through financial performance as an intervening variable in manufacturing companies for the period 2017-2023. This analysis is a study with a quantitative approach, has a population of 205 companies, with a purposive sampling method obtained from a sample used by as many as 22 companies and analyzed using multiple linear regression analysis with the help of the SPSS 26 application. The results of this study indicate that environmental performance has a positive and significant effect on financial performance, while CSR disclosure has no effect on financial performance. Furthermore, environmental performance has no effect on firm value, but CSR disclosure and financial performance have a positive and significant effect on firm value. Then, financial performance plays a role in mediating the relationship between environmental performance and firm value. However, financial performance does not play a role in mediating the relationship between CSR disclosure and firm value.